E-FLIPBOOK: ENGLISH E-MODULE SEBAGAI MEDIA PEMBELAJARAN DI ERA DIGITAL UNTUK KELOMPOK KERJA GURU BAHASA INGGRIS - Trisnawati, Winda; Habibah, Nur; Lestari, Renda; Kurniawan, Ridho; Balti, Levandra; Enjelika, Sonya (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
The activity on developing the flipbook e-module for Bungo Dani English KKG teachers is a positive and useful step in educational development. Through the flipbook e-module, Bungo Dani English KKG teachers can improve their knowledge and teaching skills. It could help understand more modern and effective teaching methods. The use of technology in the form of e-module flipbooks shows adaptation to current developments and provides easier access for teachers to obtain the latest materials. This socialization activity can allow teachers to collaborate, share experiences, and exchange ideas. Flipbook e-modules can help teachers prepare lesson plans in a more structured and efficient way. It could save teachers time preparing material and optimize the teaching and learning process. The conclusion is that the socialization activity for developing flipbook e-modules for Bungo Dani English KKG teachers has great potential to improve the quality of education and teaching methods and enrich the learning experience for teachers and students.